The Effect of Creative Problem Solving Learning Model Assisted by Google Sites on Creative Thinking Ability in Geography Learning - Dewa Putra Cisnaulin; Mahmoud M. Abu Ghosh; Alfyananda Kurnia Putra (CV Bumi Spasial, 2025)
The challenges of geography learning in the 21st century are increasingly complex, especially in developing students' creative thinking skills to face the dynamics of globalization and rapid environmental changes. The Creative Problem Solving (CPS) model is able to be an effective solution to encourage students to think innovatively and creatively in solving geography problems. The purpose of this study is to find out how the use of the Creative Problem-Solving model supported by Google Sites affects students' ability to think creatively on disaster mitigation materials. Quasi-experiment is applied as a method with a type of nonequivalent control group design. This study involved two groups of students from XI Social Science MAN Batu City. 36 students from class XI Social Science 1 were used for the experimental class and 36 students from XI Social Science 4 were used as group classes. Using 9 essay questions as a post-test test. The results of the study explained that creative t hinking skills in disaster mitigation materials are significantly influenced by the Creative Problem-Solving model assisted by Google Sites, especially on fluency and originality, thereby improving students' ability to analyze, plan, and implement effective solutions to a disaster.